PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Novianti Ni Komang; Muliati Ni Ketut (Hita Akuntansi dan Keuangan, 2022)
Firm value is the evaluation shown by the financial statements. The purpose behind this research is to see how the influence of Liquidity and Firm Size on Firm Value. The population in this study is the Automotive and Component Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2015 – 2019 as many as 13 companies. This research is a quantitative exploration. The procedure for determining the sample is by purposive sampling, so that the sample obtained is 45 samples from 9 companies. The analytical techniques used are Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, Coefficient of Determination Test (R2), and t-test. Based on the analysis test results obtained, Liquidity and Firm Size have a positive and significant impact on Firm Value.